Characterization of moderate ash‐and‐gas explosions at Santiaguito volcano, Guatemala, from infrasound waveform inversion and thermal infrared measurements. Issue 12 (27th June 2016) - Angelis, S. De; Lamb, O. D.; Lamur, A.; Hornby, A. J.; von Aulock, F. W.; Chigna, G.; Lavallée, Y.; Rietbrock, A.
Abstract: The rapid discharge of gas and rock fragments during volcanic eruptions generates acoustic infrasound. Here we present results from the inversion of infrasound signals associated with small and moderate gas‐and‐ash explosions at Santiaguito volcano, Guatemala, to retrieve the time history of mass eruption rate at the vent. Acoustic waveform inversion is complemented by analyses of thermal infrared imagery to constrain the volume and rise dynamics of the eruption plume. Finally, we combine results from the two methods in order to assess the bulk density of the erupted mixture, constrain the timing of the transition from a momentum‐driven jet to a buoyant plume, and to evaluate the relative volume fractions of ash and gas during the initial thrust phase. Our results demonstrate that eruptive plumes associated with small‐to‐moderate size explosions at Santiaguito only carry minor fractions of ash, suggesting that these events may not involve extensive magma fragmentation in the conduit. Key Points: Infrasound waveform inversion allows assessing source parameters of volcanic explosions Thermal infrared imagery allows investigating the transition from an initial gas thrust phase to a buoyant plume during volcanic eruptions Eruption plumes produced by small‐to‐moderate eruptions at Santiaguito are gas rich